The comparative effects of quertulin and adrenoblocators oral geles on the biochemical indices of rat serum after common action adrenaline and lincomycin - Borisenko, A. V.; Kononova, O. V.; Levitsky, A. P. (Journal of Education, Health and Sport, 2017)
Aim: To compare action of quertulin and adrenoblocators oral geles on the biochemical indices of rat serum after common action adrenaline and lincomycin. Methods: Adrenaline stress was made by oral application of gel with adrenalin in dose 0,36 mg/kg during 10 days. Lincomycin was introduced with drinking water in dose 60 mg/kg. The gel of quertulin was introduced by application in dose 20,34 mg/kg and the gel of adrenoblocators (zocson + nicergolin and sibason) by application in dose 0,6 mg/kg. Conents of glucose, triglycerides, total cholesterine and malonic dialdehide (MDA), the activities of urease, lysozyme, elastase and catalase were determined into serum. Results: Both geles no influenced on the serum conten glucose and triglycerides, but raised the content cholesterine. The adrenoblocator gel reduced activity urease and content MDA, but raised activity catalase. The quertulin gel reduced the activity elastase and raised the activity catalase. Conclusion: Oral application of gel with adrenoblocators made antidysbiotic action more then quertulyne, but yielded in antiinflammation and antioxidative actions to quertulyne after common introduce adrenaline and lincomycin.